2016
DOI: 10.1016/j.ejenta.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The broad base columellar strut for correction of retracted columella and under rotated tip

Abstract: Objective: To describe the technique and to detect the efficacy of the broad base columellar strut in correcting retracted columella and under rotated nasal tip. Design: Retrospective chart review. Setting: University-affiliated medical center. Methods: The charts and photographs of patients suffering from columellar retraction with acute columellar-labial angle were reviewed. The columellar-labial angle and the nasal tip projection were measured and calculated from the photos and the columellar show was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In addition, we found that there is significant role of strut graft in maintaining nasal tip projection, which is similar with Rod J. Rohrich 6 study that strut graft does not necessarily increase the nasal tip projection. We agreed with Vuyk etal 7 study that the strut graft helps to maintain nasal tip projection as well as Amr N. Rabie 4 and Mohammad Sadeghi 8 studies. Moreover, in our study we found there are strong relationship between strut graft implantation and nasal tip projection (p-value 0.016).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, we found that there is significant role of strut graft in maintaining nasal tip projection, which is similar with Rod J. Rohrich 6 study that strut graft does not necessarily increase the nasal tip projection. We agreed with Vuyk etal 7 study that the strut graft helps to maintain nasal tip projection as well as Amr N. Rabie 4 and Mohammad Sadeghi 8 studies. Moreover, in our study we found there are strong relationship between strut graft implantation and nasal tip projection (p-value 0.016).…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, columellar strut graft was used as a dominant procedure for controlling tip projection, tip rotation with minor contribution of suture technique and cartilage resection. The age of patients participating in this study ranged from 16 to 46 with a mean of 26 years similar to the study of Amr N. Rabie 4 in which patients age ranged from 19-49 with mean of 30.2 years. While Koen Ingels 5 , Rod J. Rohric 6 studies did not mention any link to age distribution.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations